Strengthening the reporting of observational studies in epidemiology using mendelian randomisation (STROBE-MR): explanation and elaboration - Skrivankova, Veronika W; Richmond, Rebecca C; Woolf, Benjamin A R; Davies, Neil M; Swanson, Sonja A; VanderWeele, Tyler J; Timpson, Nicholas J; Higgins, Julian P T; Dimou, Niki; Langenberg, Claudia; Loder, Elizabeth W; Golub, Robert M; et al. (BMJ (Online), 2021)
Mendelian randomisation (MR) studies allow a better understanding of the causal effects of modifiable exposures on health outcomes, but the published evidence is often hampered by inadequate reporting. Reporting guidelines help authors effectively communicate all critical information about what was done and what was found. STROBE-MR (strengthening the reporting of observational studies in epidemiology using mendelian randomisation) assists authors in reporting their MR research clearly and transparently. Adopting STROBE-MR should help readers, reviewers, and journal editors evaluate the quality of published MR studies. This article explains the 20 items of the STROBE-MR checklist, along with their meaning and rationale, using terms defined in a glossary. Examples of transparent reporting are used for each item to illustrate best practices.